Melkersson-Rosenthal syndrome: a retrospective study of 44 patients. (September 2014) - Feng, Shui; Yin, Jinshu; Li, Jiandong; Song, Zhiyao; Zhao, Guomin
Abstract Conclusion: When patients with recurrent facial paralysis are encountered, otolaryngologists should check for fissured tongue, and question those patients about orofacial edema, minor symptoms, and family history. Histologic evidence is not necessary for the diagnosis of Melkersson-Rosenthal syndrome (MRS), while coronary high-resolution CT (HRCT) reconstruction of temporal bone and food allergen detection may be beneficial. Prophylactic decompression of the facial nerve for patients with appropriate electrophysiological indication may prevent further facial palsy attacks. Objectives: The objective of this study was to analyze the clinical features of a group of patients with MRS with major complaints of facial palsy treated at the Department of Otorhinolaryngology, and to comment on MRS from the perspective of otolaryngologists. Methods: A retrospective review of patient database for the last 6 years in the Department of Otorhinolaryngology in Beijing Shijitan Hospital was performed to find patients diagnosed with MRS. Results: A total of 44 MRS patients were included in this study. The mean age at onset was 14.1 years. A total of 13 (29.5%) patients had family history, 17 (38.6%) revealed broadened fallopian canal on coronary HRCT reconstruction of temporal bone, and 20/23 (87.0%) patients showed positive results in food allergen detection. Thirty-one patients accepted subtotal facial nerve decompression and only one patient had facial palsy recurrence on the same side as the operation.